PJMHS 2022
DOI: 10.53350/pjmhs22166485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Strength Parameters in Amputee Football Players According to the Degree of Amputation

Abstract: Background: Amputee football is a sports branch for the disabled that has become popular in recent years. However, studies on determining and improving the performance parameters of amputee football players are limited. Aim: The purpose of this study is to compare the strength parameters of amputee football players (AF) depending on the degree of amputation. Methods: 35 amputee football players aged 16-48 years, actively participating in amputee football superleague, participated in our study. Descriptive rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…In this cross-sectional study, the required sample size was estimated based on a previous study conducted by Kurtoğlu et al [ 17 ] in which the ECHO findings of football players was reported to be 50.91 ± 4.01 mm. Thus, we performed a power analysis using a significance level (α) of 0.05, power (1-β) of 0.80, and effect size of 0.86.…”
Section: Methodsmentioning
confidence: 99%
“…In this cross-sectional study, the required sample size was estimated based on a previous study conducted by Kurtoğlu et al [ 17 ] in which the ECHO findings of football players was reported to be 50.91 ± 4.01 mm. Thus, we performed a power analysis using a significance level (α) of 0.05, power (1-β) of 0.80, and effect size of 0.86.…”
Section: Methodsmentioning
confidence: 99%
“…As dificuldades psicológicas estão relacionadas principalmente às alterações psicossociais provenientes das dificuldades de ajuste à prótese, reinserção ocupacional, rede de apoio e transtornos de imagem e função corporal, que afetam a qualidade de vida e aumentam as chances de inatividade física. 1,2,3 As dificuldades físicas estão associadas aos déficits no equilíbrio e na força muscular, 4,5 na estabilidade corporal, no controle de tronco e nos ajustes de passadas durante a marcha, 6 que têm relação direta com a capacidade de deambulação e influenciam na diminuição do nível de atividade física e, consequentemente, dos seus benefícios. 7,8 As amputações de MMII provocam alterações no gasto energético (GE), isto é, indivíduos com esta condição podem apresentar aumento do GE durante a deambulação de aproximadamente 20% da demanda no consumo de oxigênio quando comparados a indivíduos sem amputações.…”
Section: Introductionunclassified